A QbD-based stability-indicating RP-HPLC method for larotrectinib: degradation kinetics and integrated white, green, and blue analytical assessment - P. N. S, Syamala; Adikay, Sreedevi (Creative Pharma Assent, 2025)
Background: Larotrectinib, a selective TRK inhibitor, received FDA approval on April 10, 2025, for treating solid tumors with NTRK gene fusions. Despite its therapeutic significance, no RP-HPLC method using a Quality-by-Design (QbD) framework has been reported. This study aimed to develop and validate a QbD-based RP-HPLC method for larotrectinib estimation. Methodology: Critical Analytical Parameters (CAPs) were identified using a Plackett–Burman Design and optimized via a Central Composite Design (CCD). Separation was achieved on a Sunfire C18 column (250 × 4.6 mm, 5 µm) with a mobile phase of 0.1% OPA and acetonitrile (70:30, v/v), flow rate 1.0 mL/min, injection volume 10 µL, and detection at 262 nm. Optimized conditions from the Method Operable Design Region (MODR) gave a desirability value of 1. Results and Discussion: The method achieved sharp separation with a retention time of 2.2 min in a 5-minute runtime. Validation per ICH Q2(R1) confirmed linearity (12.5–75 µg/mL, R² = 0.9998), intra- and inter-day precision (%RSD < 2%), mean recovery of 99.29%, and sensitivity with DL 0.30 µg/mL and QL 0.92 µg/mL. Forced degradation studies revealed zero-order kinetics under 0.1 N HCl, 0.5 N NaOH, and thermal stress, and first-order kinetics under 0.5 N HCl, 0.1N NaOH, 3% and 5% H₂O₂, and water. Greenness, blueness, whiteness, and sustainability were assessed using AMGS, AGREE, ComplexMoGAPI, BAGI, RGB, and EVG tools, yielding favourable outcomes. Conclusion: The developed QbD-based RP-HPLC method is robust, validated, and stability-indicating, suitable for quality control, regulatory submissions, and bioanalysis of larotrectinib.